Deschampsia danthonioides (Poaceae – Pooideae) a New Record for Peruvian Flora - Gonzáles, Paúl (2011)
We report for the first time the presence of Deschampsia danthonioides (Trin.) Munro (Poaceae, Pooiideae) in the grasslands of the Lima department. Also this finding represents the first record of the genus Deschampsia for Peru.